2020
DOI: 10.3390/ma13122682
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Comparison of Macrophage Polarization and Osteoblast Differentiation Potentials between Granules and Block Forms of Deproteinized Bovine Bone Mineral

Abstract: Deproteinized bovine bone mineral (DBBM) bone grafts are commonly utilized for guided bone regeneration (GBR) techniques in regenerative dentistry. It has been hypothesized that different forms (blocks versus particulates) might demonstrate the varying properties of cell behavior during the regenerative process. Therefore, the aim of the present study was to investigate DBBM granules and blocks for their effects on osteoblasts and macrophages (Mφs). DBBM granules and blocks were filled to the same size (φ6.4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In the present study, however, the granules used were standardized throughout the experiments by utilizing the volume-based defect filling size concept instead of the weight-based concept. This approach was intended to increase the similarity of the experimental procedures to the clinical reality of the bone augmentation procedure [15]. The micro-CT imaging analysis revealed that the smaller granules showed higher material volumes and surface areas than the larger granules, as expected (Figs.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In the present study, however, the granules used were standardized throughout the experiments by utilizing the volume-based defect filling size concept instead of the weight-based concept. This approach was intended to increase the similarity of the experimental procedures to the clinical reality of the bone augmentation procedure [15]. The micro-CT imaging analysis revealed that the smaller granules showed higher material volumes and surface areas than the larger granules, as expected (Figs.…”
Section: Discussionmentioning
confidence: 54%
“…3 and 4). DBBM granules have previously been shown to drive polarization toward the M2 phenotype, as indicated by high expression of CD163 and CD206 in the murinederived macrophage cell line RAW 264.7 and by high expression of IL-10, Arginase 1 (Arg1), and CD206 in THP-1 cellderived Mφs [15,20]. BCP has been reported to upregulate the gene expression of most inflammatory factors and growth factors in RAW 264.7 cells [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primers need to be designed using NCBI-nucleotide library and Primer3-design in order to detect messenger RNA (mRNA) of the targeted genes. In Table 1 a list of the most useful primer sequences for the amplification of cDNA by real-time PCR is presented [50,51]. RT-qPCR can now be performed with the cDNA extracted from the cells and the designed primers.…”
Section: Osteoblasts Differentiationmentioning
confidence: 99%
“…RT-qPCR can be used in order to detect differences in the expressions of M1 and M2 markers. For M1 profile; IL-1, IL-6 and TNF-α are normally explored; whereas for M2 markers IL-10, Arg1, CD206 and TGF-β are the selected genes [51,67]. Recommended genes' sequences are presented in Table 2 [51,67].…”
Section: Macrophages Polarization Testingmentioning
confidence: 99%